Active Microstrip Antenna Design for Global Positioning System Application - Thiagarajah, Sharlene (2000)
A circularly polarized microstrip antenna (MSA) was investigated for a commercial land-based Global Positioning System (GPS) application. Critical GPS antenna requirements are its gain, polarization and radiation characteristics. Advancements in electronic miniaturization techniques have made GPS receivers smaller and less bulky, paving the way for smaller antenna structures to improve aesthetic appearance. The crossed-drooping dipole, conventional and printed quadrifilar helix (QHA), archimedean spiral, conical spiral, printed cylindrical slot and the microstrip antenna were investigated for their circular polarization potential and broad beamwidth. Performance comparison analysis indicated the microstrip antenna as a suitable choice mainly for its simple design structure and attractive physical properties. Two patch geometry, the circular and square patch antennas were fabricated and analyzed to investigate the MSA's design and fabrication sensitivity to geometry. Performance degradation due to fabrication tolerances is an important issue in manufacturing. Experimental results showed good impedance matching and similar patch performance for both patches. The effect of patch size was also investigated using two different substrates. The only limitation of the MSA for GPS application was its low gain characteristic. However this was easily overcome by integrating an active circuit with the patch. A 16dB increase in gain was obtained without affecting its other performance parameters or low profile structure. GPS satellite acquisition measurements showed that the proposed active antenna could track satellites even at low elevation angles. To further improve the axial ratio performance of the patch antenna, the effects of limited groundplane at GPS frequency Ll were investigated. Best axial ratio was obtained when groundplane surrounding radiating patch was kept as small as possible. Radiation pattern became omnidirectional but with lower gain characteristics. Attaching parasitic to patch periphery improved axial ratio but reduced gain further. The proposed omnidirectional antenna could find good use for GPS marine applications. In conclusion the proposed active MSA is seen as a good candidate for commercial GPS applications. Its simple patch design is easy to fabricate and duplicate for mass production.